InfoAdviser - Azmi, Muhammad Haikal; Alif Nizam, Mohammad Nur Daniel; Wan Samsudin, Wan Arif Hakimi; Fadzil, Muhammad Farhan; Arif, Zuraidah (Universiti Teknologi Mara, Kedah, 2022)
InfoAdviser is an information-searching application focusing on the latest issues. InfoAdviser offers advice from information experts on the latest issues and quality (good) information from reliable information sources. The purpose of the InfoAdviser is to use the library as an information expert to serve the community with reliable sources. The issue that motivates the project is lots of issues about misleading information. The InfoAdviser take Service Innovation Model by Den Hertog and the Uses and Gratification Theory by Blumer and Katz. The service innovation model comprises six-dimension signalling user needs and technological options; conceptualising; (un-)bundling; co-producing and orchestrating; scaling and stretching; and learning and adapting. The use and gratification focus on the needs, motives, and gratifications as a motive in using media. Based on the service innovation model and use and gratification theory, the InfoAdviser is proposed to address the issue. The InfoAdviser is an easy-to-use application that provides information on the latest issue by combining search results from the library WebOpac, news, research articles, data and statistics, and videos. The InfoAdviser offers information quality (selected and evaluated by an information expert) and combines information resources for the community based on their need. The InfoAdviser is a shift in providing information services to users by highlighting the information sources based on information search. The InfoAdviser offers information services based on users' information needs by minimizing the need for library orientation by providing an application that is simple and easy to use without needing much time to learn about the site.